GEOLOGICAL EVALUATION OF STRUCTURAL DEFORMATION OF THE TAWAR FORMATION, ACEH TENGAH, INDONESIA - Widiyani, Arrival Fadila; Gunawan, M. Ridho Gifaro; Tanzir, M.; Adhari, Muhammad Ridha (Universitas Mataram, 2024)
Lake Lut Tawar, which is situated in Aceh Tengah, has a unique geological landscape, with the presence of rock formations of the Pre-Tertiary age (Tawar Formation) and its geological connection with the Sumatran fault and the Bukit Barisan mountains. Even though the geological condition of the Lut Tawar Lake has attracted the attention of many geologists to carry out various kinds of research, there is still a lot of geological understanding that is not yet known, especially regarding the Tawar Formation. Tawar Formation is of Pre-Tertiary age and can be found around Lut Tawar Lake, Aceh Tengah. This research targeted the Tawar Formation with two main objectives: (1) to evaluate structural deformation and geologic structures developed within the Tawar Formation and (2) to understand better the main factors influencing the evolution of the Tawar Formation. Integrated geological analyses, including structural geology analysis, scanline method, and stereo net method, were used to achieve the objectives of this research. Results from this study show that the Tawar Formation has experienced a complex structural deformation, evidenced by the presence of various geological structures such as multi-size and multi-episode fracture systems and numerous folds and faults. Furthermore, we interpret the evolution of the Tawar Formation to be strongly influenced by tectonic activity, possibly related to the movement of the Sibumasu plate, the Sumatran fault system, and plate subduction in the southwest part of Sumatra. It is expected that the results of this research will provide a new understanding of the history and evolution of the Tawar Formation and a better understanding of the deformation of rock structures that occurred in the Lut Tawar area, Aceh Tengah. Â